Norms and the State in China - Huang, Junjie; Zürcher, Erik (BRILL, 1993)
The central theme of this volume is the Chinese concept of chiao-hua, "Transformation by Instruction": the ancient idea that moral guidance in all spheres of life is one of the most essential tasks of leadership at all levels, from the central government down to local elites. Within this general perspective nineteen scholars of various disciplinary backgrounds have treated topics ranging from the regulation of conspicuous consumption in Ming times to ritualization of protest in recent times. In many cases a surprising degree of cultural continuity can be observed; on the other hand, due attention has also been paid to clashes between traditional Chinese (notably Confucian) norms and the demands of modernization in contemporary Chinese society
Includes bibliographical references and index